Working Capital and Profitability in Two Wheeler Industry: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The efficiency of a firm depends largely on its ability to manage its working capital. Its effective provision can ensure the success of a business while its inefficient management can lead not only to loss but also to ultimate downfall of what otherwise might be considered as a promising concern. So, the working capital management aims at achieving a trade-off between liquidity and profitability goals. In the present study, an attempt has been made to analyze the extent up to which twin goals have been attained in Indian two-wheelers industry.